Assessing and enhancing the impact potential of marketing articles - Jaakkola Elina; Vargo Stephen L. (Springer, 2022)
Although the impact of marketing is a recognized priority, current academic practices do not fully support this goal. A research manuscript’s likely influence is difficult to evaluate prior to publication, and audiences differ in their understandings of what “impact” means. This article develops a set of criteria for assessing and enhancing a publication’s impact potential. An article is argued to have greater influence if it changes many stakeholders’ understandings or behaviors on a relevant matter; and makes its message accessible by offering simple and clear findings and translating them into actionable implications. These drivers are operationalized as a checklist of criteria for authors, reviewers, and research supervisors who wish to evaluate and enhance a manuscript’s potential impact. This article invites scholars to further develop and promote these criteria and to participate in establishing impact evaluation as an institutionalized practice within marketing academia.